2014
DOI: 10.1002/etc.2572
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the bioconcentration factor in common carp (Cyprinus carpio L.) using data from the dietary exposure bioaccumulation fish test

Abstract: An approach to predicting the bioconcentration factor (BCFpre ) from the predicted uptake rate constant (k1 pre ) and the depuration rate constant measured in the dietary exposure bioaccumulation fish test (k2 dietary ) [BCFpre  = k1 pre /k2 dietary ] is proposed in test guideline 305 of the Organization for Economic Cooperation and Development Guidelines for Testing of Chemicals. Data were collected on the BCFs of 197 test chemicals from Japan's Chemical Substances Control Law database. To demonstrate how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Six of Japan's good laboratory practice [15] laboratories volunteered to conduct the studies for the ring test. The BMF kgL values for HCB in common carp in previous studies have been reported to be higher than 1 [10][11][12], but the BMF kgL values in the ring test were below 1 for all 6 laboratories. The results revealed that the lipid-corrected, growth-corrected kinetic BMF (BMF kgL ) varied by more than a factor of 10 between the laboratories (BMF kgL 0.065-0.82, average 0.32, median 0.24).…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…Six of Japan's good laboratory practice [15] laboratories volunteered to conduct the studies for the ring test. The BMF kgL values for HCB in common carp in previous studies have been reported to be higher than 1 [10][11][12], but the BMF kgL values in the ring test were below 1 for all 6 laboratories. The results revealed that the lipid-corrected, growth-corrected kinetic BMF (BMF kgL ) varied by more than a factor of 10 between the laboratories (BMF kgL 0.065-0.82, average 0.32, median 0.24).…”
Section: Introductionmentioning
confidence: 59%
“…The results revealed that the lipid-corrected, growth-corrected kinetic BMF (BMF kgL ) varied by more than a factor of 10 between the laboratories (BMF kgL 0.065-0.82, average 0.32, median 0.24). The BMF kgL values for HCB in common carp in previous studies have been reported to be higher than 1 [10][11][12], but the BMF kgL values in the ring test were below 1 for all 6 laboratories. The main differences in the test conditions between the ring test and previous studies [10][11][12] were the test food and feeding rate, both of which might have affected the BMF kgL value.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations